Avaliação do reaproveitamento dos efluentes gerados por sistemas de tratamento de água para hemodiálise - Faria, Paulo Gil Siqueira de (2018)
Reverse Osmosis systems are used in Hemodialysis clinics. These systems generate an effluent volume called reject or concentrate. In addition, the pretreatment composed of sedimentation filter, softener filter and activated carbon filter, discard the water used in backwash for filter maintenance. The present study evaluated the reuse of the effluents generated by this system in two hemodialysis clinics in the city of Curitiba / PR. In the first clinic, effluents from the backwashing of the sedimentation filter and activated carbon filter were reused in toilet and in the cleaning of external patios, and the effluent generated by the softening filter was discarded. In both clinics, Reverse Osmosis systems for Rejection treatment (ORR) were installed. Through this effluent recovery system, it was possible to reduce water discharges from 49% to 16%, the volume used in the therapies went from 42% to 70% and other consumptions, which accounted for 9%, remained at 14% of the total used in supplying the clinic. The use of the ORR allowed to recover 80% of the waste to feed back the own Water Treatment Subsystem for Hemodialysis (STAH) and the remainder was directed to use in the toilets and for external cleaning, with 100% of the wastewater recovered. Qualitatively, the liquid recovered by the ORR has low solutes concentration and conductivity less than 5μS. Microbiological levels were below the maximum limit for heteretrophic bacteria, total coliforms and endotoxins determined by the National Agency of Sanitary Surveillance (ANVISA) through Resolution of the Collegiate Board of Directors RDC 11/2014, which establishes safety standards for hemodialysis. The water from the backsets is compatible with the established purpose for reuse in toilets and yard cleanings.